Pressing iron ore concentrate in a pilot-scale HPGR. Part 1: Experimental results. (15th August 2019) - Campos, Tulio M.; Bueno, Gilvandro; Barrios, Gabriel K.P.; Tavares, Luís Marcelo
Graphical abstract: Highlights: Throughput drops as specific force increases. A parabolic profile appears in Blaine and %-45 µm along the rolls. Moister feeds led to smaller operating gaps and higher energy absorption. Moister feeds led to a more limited edge effect. Efficiency dropped for higher velocities and finer feeds. Abstract: Much practical experience has been gathered along the nearly thirty years of application of high-pressure grinding rolls (HPGRs), also called roller presses, in size reduction of iron ore concentrates prior to pelletization. In spite of this, relatively limited experimental data exists from tests conducted under controlled conditions in a large enough scale that allows understanding the influence of several of the process variables on the comminution performance. The paper analyzes tests with an iron ore concentrate sample carried out over a range of pressures, roll velocities, feed size distributions and moisture contents in a pilot-scale facility. It is observed that specific throughput drops as the operating pressure is increased, a parabolic profile appears along the rolls regarding both Blaine specific surface area (BSA) and percent passing 0.045 mm, and also that operation at higher moistures resulted in smaller gaps, higher specific energy absorption and higher BSA. The ratio between the surface area created and the energy consumption was generally found to be relatively constant for different operating conditions, only reducing for higher roll speeds and finer feeds. A model for estimating BSA on the basis of the size distributions has also been successfully fitted.